Guidelines to the Practice of Anesthesia – Revised Edition 2018 - Dobson, Gregory; Chong, Matthew; Chow, Lorraine; Flexman, Alana; Kurrek, Matthew; Laflamme, Claude; Lagacé, Annie; Stacey, Shean; Thiessen, Barton (Canadian journal of anesthesia, 2018)
Overview The Guidelines to the Practice of Anesthesia Revised Edition 2018 (the Guidelines) were prepared by the Canadian Anesthesiologists’ Society (CAS), which reserves the right to determine their publication and distribution. The Guidelines are subject to revision and updated versions are published annually. The Guidelines to the Practice of Anesthesia Revised Edition 2018 supersedes all previously published versions of this document. Although the CAS encourages Canadian anesthesiologists to adhere to its practice guidelines to ensure high-quality patient care, the CAS cannot guarantee any specific patient outcome. Anesthesiologists should exercise their own professional judgement in determining the proper course of action for any patient’s circumstances. The CAS assumes no responsibility or liability for any error or omission arising from the use of any information contained in its Guidelines to the Practice of Anesthesia.